SPIN-01 RADIATION THERAPY ALONE VERSUS RADIATION THERAPY PLUS RADIOFREQUENCY ABLATION/VERTEBRAL AUGMENTATION FOR SPINE METASTASIS: TRIAL IN PROGRESS. (5th August 2022) - Kotecha, Rupesh; Schiro, Brian; Sporrer, Justin; Rubens, Muni; Avendano, Maria; Appel, Haley; Tom, Martin; Mehta, Minesh
Abstract: BACKGROUND: Spine metastases are a common occurrence in cancer patients and result in pain, neurologic deficits, decline in performance status, disability, inferior quality of life (QOL), and reduction in ability to receive cancer-directed therapies. Conventional external beam radiation therapy (EBRT) is associated with modest rates of pain relief, high rates of disease recurrence, low response rates for those with radioresistant histologies, and limited improvement in neurologic deficits. The addition of radiofrequency ablation/percutaneous vertebral augmentation (RFA/PVA) to index sites together with EBRT may improve pain response rates and corresponding quality of life. METHODS/DESIGN: This is a single-center, prospective, randomized, controlled trial in patients with spine metastases from T5-L5, stratified according to tumor type (radioresistant vs. radiosensitive) in which patients in each stratum are randomized in a 2:1 ratio to either RFA/PVA and EBRT or EBRT alone. All patients are treated with EBRT to a dose of 20-30 Gy in 5-10 fractions. The target parameters are measured and recorded at the baseline clinic visit, and daily at home with collection of weekly measurements at 1, 2, and 3 weeks after treatment, and at 3, 6, 12, and 24 months following treatment with imaging and QOL assessments. DISCUSSION: The primary objective of this randomized trial is to determine whether RFA/PVA in addition to EBRT improves pain control compared to palliative EBRT alone for patients with spine metastases, defined as complete or partial pain relief (measured using the Numerical Rating Pain Scale [NRPS]) at 3 months. Secondary objectives include determining whether combined modality treatment improves the rapidity of pain response, duration of pain response, patient reported pain impact, health utility, and overall QOL. The results from this study will be used to allow for comparisons to alternative treatment approaches. This trial was activated 5/2020 and is open to accrual.